Preoperative diagnosis of Mycobacterium avium lymphadenitis in two immunocompetent children by polymerase chain reaction of gastric aspirates - Haas, Walter; Amthor, Beate; Engelmann, Guido; Rimek, Dagmar; Bremer, Hans J. (The pediatric infectious disease journal, 1998)
Background. - Analysis of gastric aspirates is a routine procedure for detection of Mycobacterium tuberculosis in pediatric pulmonary tuberculosis. However, identification of nontuberculous mycobacteria in gastric aspirates of immunocompetent children is not thought to be clinically significant. - Methods. - A PCR method was devised for the detection of M. avium in clinical specimens. The method is based on the amplification of a M. avium-specific DNA fragment present in the 3′-end of the repetitive element IS1245. Surgically removed lymphatic tissue was analyzed prospectively by microscopy, culture and PCR in 13 children admitted to our hospital with suspected mycobacterial lymphadenitis. In 4 of these children 1 to 4 gastric aspirates were obtained before surgical treatment and submitted to the same analysis. -Results. -We report the detection of M. avium in the gastric aspirates of two children with cervical lymphadenitis before surgical intervention by a novel PCR method. The subsequently surgically removed lymph nodes were also positive by PCR and culture. In one child cultures of both sources grew M. avium. The isolates could be identified as the same strain by DNA fingerprinting. The PCR assay was almost twice as sensitive as culture in detecting M. avium. - Conclusions. - Our findings suggest the possibility for noninvasive diagnosis of cervical lymphadenitis caused by nontuberculous mycobacteria before surgery. In addition detection of M. avium in gastric aspirates without evidence of fistula formation provides new insights into the pathogenesis of mycobacterial infection and disease in immunocompetent children.
Gesehen am 19.06.2024